Introducing a podcast as a networked intervention to support first-year students’ transition into higher education:: A design-based research approach - Dorani Andersson, Saga; Jaldemark, Jimmy (Proceedings of the International Conference on Networked Learning, 2026)
This paper reports on a first-cycle educational design research study that examines a teacher-led podcast as an intervention to support first-year students’ transition into higher education. Motivated by documented early vulnerabilities and their association with withdrawal, the study investigates whether a podcast can scaffold belonging, clarify expectations, and provide early guidance during the initial phase of study. The networked learning intervention—The Behavioural Science Pod—comprised five semi-structured, dialogical episodes hosted by programme teachers and distributed via the learning management system. Drawing on the Communities of Inquiry framework, the podcast was designed to engage social, teaching, and cognitive presence. Two instruments were used to evaluate the artefact: a survey (n=35) and a focus-group (n=5) interview were used to capture both broad patterns and deeper experiences. Open-ended responses from both datasets were thematically analysed. Findings converged around four themes: usage patterns, perceived benefits, pedagogical value, and areas for improvement. A clear usage pattern emerged: just over half of respondents engaged with the podcast at least once—an uptake exceeding that reported in earlier comparable initiatives. Non-listening was attributed to both internal (e.g., lack of preference for the medium, forgetfulness, no perceived need) and external (time constraints) aspects, underscoring that podcasts are not a one-size-fits-all solution. For listeners, the primary point of use was the very start of studies, a period consistently described as uncertain and emotionally demanding. In this context, the podcast acted as a supportive networked resource that offered orientation, reassurance, and practical strategies while conveying presence and trust through its conversational tone. Students highlighted relational benefits (a felt closeness to teachers; a sense of “being part of the conversation”) alongside cognitive support, with episodes on navigating course literature and working in study groups repeatedly singled out as especially helpful. Interpreted through the Communities of Inquiry lens, the podcast fostered social presence, strengthened teaching presence, and enabled meaning-making indicative of cognitive presence. At the same time, students identified important areas for improvement: wider distribution, provision of transcripts or textual summaries for accessibility and navigation, more episodes and stronger curricular integration—potentially making selected episodes compulsory. Overall, the study demonstrates that a carefully designed podcast can provide low-threshold, multidimensional networked support for first-year students’ transition, while also revealing design constraints and inclusion requirements. The paper contributes practical design rationales and a theoretically informed account of podcasting’s affordances and limitations, and it outlines a forthcoming study that will examine a podcast as the primary medium for an entire course.